The family in the hospital context: learning about the yearnings and - Juliana Padial Miliorini; Marina Viana Fernandes; Maria das Neves Decesaro; Sonia Silva Marcon (Rev Rene)
This is an exploratory descriptive research with a qualitative approach, based on the analysis approach proposed by Bardin, aiming to identify yearnings and expectations caused by chronic disease in the family. The sample was constituted by four families with members who had chronic diseases, who were care dependent for over three months and under fi ve years, and who were in a University hospital. Data collection was carried out from September to November 2007. Results allowed the identifi cation of three categories: showing the understanding of the disease; disclosing the wistfulness regarding the unfolding of the disease and having a glimpse of expectations regarding home care. We considered that nursing, when delivering intra hospital care, should include the family approaching the pathology understanding as indispensable for the learning about health-disease, strategically adopting the empathic relationship to favor communication between patient and family.